(Unaccompanied) Young Migrants and Football: Mediating a ‘Safe Space’ for Enhancing Subjectivities Systems - Elia, Anna; Fedele, Valentina (Italian Sociological Review, 2021)
The article focuses on the relationship between young migrants arriving as unaccompanied minors and hosted in SIPROIMI residential community and football, focusing, on the one hand, on the possibility for football to foster young migrants’ insertion path in host countries, on the other hand, on the space football offers for young migrants to articulate their subjectivity. The reflection proposed is based on the preliminary results of a qualitative field research that involved four SIPROIMI centres in Calabria, between May and September 2020. Taking into account both the literature on sport and social capital concerning people with forced migration background, and the specific literature on accompanied migrants’ insertion path in hosting centres, the analysis sustains that, while the nexus between football and the production of social capital sustaining their integration is questioned, it represents a safe space for young migrants’ subjectivities to be expressed and enhanced.